PEMAHAMAN HADIS KONSERVASI LINGKUNGAN DAN INTERNALISASINYA PADA CIVITAS AKADEMIKA PROGRAM STUDI ILMU HADIS IAIN KEDIRI - Umi Hanik; Ibnu Hajar Ansori; A Zahid (Prodi Sosiologi Agama, 2021)
As part of the ecological system, humans have a dominant role in determining the good and bad of the environment. The stability and comfort of the environment depend on the positive behavior around the elements of the ecosystem in it, including humans. The emergence of various environmental problems is also inseparable from human indiscipline in protecting and preserving them. An environment that is maintained properly, will respond positively by providing great benefits to humans. Otherwise, an environment that is treated badly will repay with damage and disaster. The leadership of the Faculty of Ushuluddin and Da'wah at IAIN Kediri was fully aware of this, especially the Hadith Science Study Program. This awareness forms a religious construction based on an understanding of religious texts, particularly Hadith. Through qualitative research, this reality will be described descriptively and analytically. The results illustrate that the epitome construction of environmental conservation activities is manifested in participation in the Green Campus program. The sociological construction contestation was seen in the leadership of the Hadith Science Study Program and the academic community for the absorption of religious teaching, thus generating practices in the form of involvement in tree and flower planting activities in the Faculty of Ushuluddin and Da'wah.